Outside the universe - Hamilton, Edmond, 1904-1977; Senf, C. C. (Curtis Charles), 1873-1949 (Salt Lake City, UT : Project Gutenberg, 2024)
"Outside the Universe" by Edmond Hamilton is a science fiction novel written in the late 1920s. The story unfolds in a universe where the Interstellar Patrol, composed of various alien races, faces an unprecedented threat from a swarm of alien ships emerging from the depths of outer space. The protagonist, Captain Dur Nal, along with his crew, including lieutenants Korus Kan and Jhul Din, must confront this formidable cosmic challenge that could annihilate their galaxy. At the start of the narrative, the reader is thrust directly into a chaotic scene aboard a patrol ship as it navigates through treacherous ether-currents in deep space. The protagonist discovers a meteoric swarm approaching their galaxy, only to realize it's not meteors but a massive fleet of alien vessels equipped with deadly weapons. A fierce battle ensues, resulting in the destruction of most of Nal's squadron. However, they manage to capture one of the alien ships, the thought of which sets the stage for a daring mission to seek help from the Andromeda universe against the looming threat of invasion. This gripping opening engages the reader with its imaginative cosmic elements, vibrant alien characters, and high-stakes adventure. (This is an automatically generated summary.)
Release date is 2024-07-11
Greg Weeks, Mary Meehan and the Online Distributed Proofreading Team at http://www.pgdp.net
Keywords: Science fiction; Adventure stories; Space warfare -- Fiction